(untitled) (Al-Academy, 2026)
Throughout the twentieth century, the abundance of artistic movements originating from different places appears, including such as surrealism and cubism from the Soviet Union and France as well as the realism approach as one of the leading trends. The emergence of this artistic revolution has been, to a great extent, a result of the by play of political, social and economic factors. These currents and schools of thought have found varied artworks that capture the fundamental rethinking and reality transformation in human consciousness and society. The following century’s art movements were shaped by the political contexts in the interwar period, the economic clashes and the cultural conflicts, which eventuated to the desire for a new identity and art’s liberation from its traditional fetters. For instance, the surrealism as a protest movement rises in response to the social and political turmoil of the times, as people seek refuge from this tragedy by unconsciously dreaming. Moreover, art movements experience conversions in trajectories as a response to politics which coincide with evolution of culture and society. This time of great disruptions was characterized by the transformation of structures and principles of the societies where artists tried new ways to portray this change, and this new art dealt with the issues raised by this transition. For example, the cubism movement was responsible for the replacing of complex natural shapes with geometric forms to reflect the changes of the industrial period and the progress with city life. To start with, what the last century´s art development led to was not a matter of political and social factors having on their own, but of a much more complex matter, the one related to these mentioned factors and to economics and culture. Through the research of those movements and art schools, we go deeper into studying the proponents which were the driving forces to the artistic and cultural life during the last century, and which reflect on the character of art as well as society nowadays.